Answer:
x = 2
Step-by-step explanation:
To simplify the given equation:
(15/x - 5) - 5 = (21/x - 6) - 7
First, let's simplify the algebraic expressions within the parentheses.
(15/x - 10) = (21/x - 13)
Now, let's multiply both sides of the equation by the common denominator, which is x.
x * (15/x - 10) = x * (21/x - 13)
This simplifies to:
15 - 10x = 21 - 13x
Next, let's combine like terms.
-10x + 15 = -13x + 21
Adding 10x to both sides of the equation:
15 = -3x + 21
Now, subtract 21 from both sides of the equation:
15 - 21 = -3x
-6 = -3x
Finally, divide both sides by -3 to solve for x:
x = -6 / -3
Simplifying the expression, we find:
(B )y = -1/3x + 6
(C) y = 3x + 3
(D) = (1/3x) - 6
Can someone help me please??
Answer:
1/2a = -5
a = (-5 x 2) : 1
a = -10
8 - b = 9,5
b = 8 - 9,5
b = -1,25
0,1 = -10c
c = 0,1 : -10
c = -0,01
I hope it's helpful.
Answer:
1998
Step-by-step explanation:
Answer:
The answer is 48
Step-by-step explanation: